Globalisasi dan Transformasi Pendidikan Digital: Kajian Literatur Komparatif Sistematis tentang Kebijakan Berbasis Teknologi di Indonesia, Korea Selatan, dan Finlandia - Rizka Dwi Aprilia; Safari; Muhammad Aridan (SAKALIMA: Pilar Pemberdayaan Masyarakat Pendidikan, 2026)
Digital education reform is often assessed through technology availability, although its sustainability depends on policy coherence, teacher agency, and equity. This comparative systematic review examines technology-based education policies in Indonesia, South Korea, and Finland and identifies transferable lessons for Indonesia. A PRISMA 2020-informed search across Scopus, ERIC, Web of Science, Google Scholar, and official international and national portals assembled 30 primary evidence sources, complemented by methodological and theoretical literature. Thematic and narrative synthesis compared policy governance, infrastructure and platforms, curriculum and teacher development, equity, and data governance. South Korea demonstrates a state-led, interoperable ecosystem supported by the Korea Education and Research Information Service, whereas Finland embeds digital competence in curriculum and teacher professionalism through locally responsive implementation. Indonesia has expanded digital platforms and reform initiatives, but regional infrastructure gaps, uneven pedagogical capacity, and fragmented implementation remain salient. The study advances a four-layer policy alignment model linking equitable access, pedagogical capacity, institutional governance, and continuous evaluation. Rather than importing a single foreign model, Indonesia should adopt context-sensitive adaptation through differentiated regional support, teacher learning communities, interoperable public platforms, and outcome-oriented monitoring. These findings position digital education as a vehicle for empowering teachers, schools, and learning communities toward inclusive quality education.